Kwazulu-Natal Income Dynamics Study (KIDS) 1993-1998: a longitudinal household data set for South African policy analysis - Haddad, Lawrence J.; Carter, Michael R.; May, Julian; Maluccio, John A. (Informa UK Limited, 2000)
An important adjunct of apartheid has been the absence of credible and comprehensive data on which policies, such as poverty reduction strategies, can be grounded. The 1993 Project for Statistics on Living Standards and Development (PSLSD) provided the first comprehensive household database for South Africa. Despite its usefulness, however, the one round PSLSD cannot provide answers to many questions important to policy researchers and practitioners, particularly questions about dynamic processes. The primary objective in this article is to introduce a new longitudinal household database, based on the PSLSD, which begins to fill this gap. Households surveyed by the PSLSD in KwaZulu-Natal province were re-surveyed in 1998 by the KwaZulu-Natal Income Dynamics Survey (KIDS). As a research endeavour, the KIDS project addresses one of the most vexing and important problems confronting contemporary South Africa: understanding the forces and mechanisms which contribute to the perpetuation of apartheid's legacy of poverty and inequality.